Development of Interactive Teaching Materials Based on Augmented Reality to Improve the Learning Outcomes of Sciences in Grade IV Students - Sinta Damayanti; Andri Valen; Citra Raflesia (CV Edujavare Publishing, 2026)
This study aims to develop Augmented Reality-based teaching materials. Testing the validity, practicality, and effectiveness of Augmented Reality-based teaching materials for fourth-grade students of SDN 30 Lubuklinggau. This type of research is Research and Development with the ADDIE development model. The subjects of this study were fourth-grade students of SDN 30 Lubuklinggau. Data collection techniques used observation, interviews, questionnaires, and tests. Based on the results of the validity of Augmented Reality-based teaching materials using Aiken's V, the language validator assessment was 0.96, the media validator was 0.83, and the material validator was 0.82. Analysis of the teacher and student practicality sheet assessments showed that Augmented Reality-based teaching materials met the criteria of being very practical with an average score of 92.24%. Then the analysis of the effectiveness assessment obtained an average N-Gain score of 0.76 with a high category. Based on the research results, it can be concluded that the Augmented Reality-based teaching materials are proven valid, practical, and effective, making them suitable for use in fourth-grade science lessons at SDN 30 Lubuklinggau. Furthermore, the developed teaching materials are expected to support a more interactive and engaging learning process for students.